Fejezetek a csehszlovák-magyar lakosságcsere dél-alföldi történetéből : Csanádalberti példája - Miklós, Péter (Közép-Európai Közlemények, 2009)
Csanádalberti village’s today lying in Csongrád (Hungary), but it was the part of the historical Csanád county before 1950. Csanádalberti founded in 1844. The first residents of the village was slovakian tobacco gardeners. The population of the village in 1941 was 1510 men, in 1949 was only 999 men. The local slowakian lutheran community’s number fallen in the 1940’s: from 1418 (1941) to 278 (1949). The slovakians of Csanádalberti settled to Czechoslovakia, they left 1500 acres fields, what distributed hungarians from Hungarian Uplands (they were settled out from Czechoslovakian between 1945 and 1948). The author used the documents of Csongrád Megyei Levéltár (Archives of Csongrád County) and the contemprary local newspapers.